2015
DOI: 10.1007/s00704-015-1526-7
|View full text |Cite
|
Sign up to set email alerts
|

Reference evapotranspiration change and its sensitivity to climate variables in southwest China

Abstract: Reference evapotranspiration (ET 0 ) is the key factor for hydrologic water balance, irrigation scheduling, and water resources planning. Based on Food and Agriculture Organization (FAO) Penman-Monteith method and the climate variables of 57 meteorological stations from 1960 to 2010 in southwest China, the spatial and temporal distributions of ET 0 were analyzed by using Mann-Kendall test and Sen's slope estimator. Sensitivity coefficient was used to analyze the sensitivities of ET 0 to four climate variables,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 34 publications
(31 reference statements)
3
37
0
Order By: Relevance
“…Over a 116-year period , Irmak et al [11] found a significant decrease in ET 0 in the Platte river basin, USA. The same declining trends were also found in other regions throughout the world, such as New Zealand (from the 1970s to the early 2000s), India , and parts of China [12][13][14]. However, an increasing trend in ET 0 was identified in other regions from the 1960s to early 2000s, such as Iran , Northern Eurasia , and parts of Romania (1961Romania ( -2007 [3,15,16].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Over a 116-year period , Irmak et al [11] found a significant decrease in ET 0 in the Platte river basin, USA. The same declining trends were also found in other regions throughout the world, such as New Zealand (from the 1970s to the early 2000s), India , and parts of China [12][13][14]. However, an increasing trend in ET 0 was identified in other regions from the 1960s to early 2000s, such as Iran , Northern Eurasia , and parts of Romania (1961Romania ( -2007 [3,15,16].…”
Section: Introductionsupporting
confidence: 65%
“…There, the sensitivity analyses for changes in the annual ET 0 showed that Ave RH and Max T were the most sensitive climate variables over the whole Songnen Grassland, which was in agreement with Yin et al [44], who studied all of China during 1961-2008. However, Liu et al [14] has reported that Win S and Sun H were the most sensitive factors in other parts of China. Therefore, it can be concluded that ET 0 has different responses to climate variables in different regions and under different climate conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Many studies have focused on spatial and temporal variations in ET 0 as well as the driving climate factors in different climatic regimes. Numerous studies have found different ET 0 trends in different regions globally, including North America, Africa, India, Argentina, Australia, Western Europe, and China (Donohue et al, ; Jhajharia et al, ; Terink et al, ; La Casa and Ovando, ; Zhao et al, ; Liu et al, ; Onyutha, ; Wang et al, ). Globally, ET 0 is decreasing, with the majority of these trends observed in Australia (Donohue et al, ), northeast India (Jhajharia et al, ), the United States (Irmak et al, ), southeast Turkey (Ozdogan and Salvucci, ), and northwest Bangladesh (Mojid et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al . () show that WS is the largest contributor to ET 0 variability, followed by Ta, SD, and RH in southwest China. Shan et al .…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al . () analysed annual PET trends for individual stations and the entire study area during 1960ā€“2010. Sun et al .…”
Section: Introductionmentioning
confidence: 99%